Relationships between personal religiosity and academic achievement among Sarawakian muslim secondary school students - Nor Hazirah, Hussin (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Personal religiosity is one's personal quality of being religious. This research investigated the relationship between personal religiosity and academic achievement among secondary school Muslim students. In this study, personal religiosity comprised of religious belief, public religious practice and private religious practice. This study was conducted using a a quantitative correlational research design. The sample in this study consisted of 306 Fonn Four Muslim students from four secondary schools in Marudi, Miri and Bintulu Divisions, Sarawak. The data was collected using a questionnaire with items having 5point Likert Scale responses. Pearson Moment Correlation analyses were conducted to determine the relationships between components of personal religiosity and academic achievement while the Multiple Linear Regression analysis was used to determine the most dominant component in personal religiosity affecting academic achievement. The findings of this study showed that there was a positive but very weak relationship between religious belief and academic achievement, and between private religious practice and academic achievement. However, there was no relationship between public religious practice and academic achievement. Only 12.2% of academic achievement was predicted by religious belief, public religious practice and private religious practice, and the strongest predictor was private religious practice followed by religious belief and public religious practice. Based on this research's finding, religiosity was one of many important factors to consider in increasing academic achievement among students. Thus, in addition to focussing on academic-based strategies to enhance students' academic achievement, focus should also be given to improving the level of religiosity among students.